Plastic deformation and mixed-mode I/II fracture behavior of un-plasticized polyvinyl chloride. (1st May 2020) - Ran, Chun; Yang, Bangcheng
Highlights: The maximum load of mode II is about 100% higher than that of mode I. Load-carrying capacity of UPVC is dependent on orientation and load condition. CTOD is the predominant controlling parameter of crack propagation. Mode I failure (opening) should be the main failure mechanism of UPVC. Abstract: To further understand the mixed-mode I/II fracture behavior of Un-plasticized Polyvinyl Chloride (UPVC), a series of mixed-mode I/II experiments on analogy compact tension specimens have been conducted using an MTS 810 hydraulic test machine. The evolution of the displacement field during stable crack extension was monitored by two-dimensional digital image correlation technique. Results obtained from the mechanical testing demonstrate that the maximum load of mode II is about 100% higher than that of mode I, and the load-carrying capacity is dependent on orientation and load condition. Fractography observations indicate that the fracture surface can be divided into fatigue region with relatively smooth characters and stable crack extension region with randomly distribution of honeycomb-like voids. Furthermore, mode I failure (opening) should be the main failure mechanism of UPVC rather than mode II (shear failure). The results also suggest that the value of crack opening displacement (COD) tends to be nearly constant when the length of crack exceeds the thickness of the sample, which is independent on orientation and load condition. Therefore, COD criterion can be used to describe the overall severity of plastic deformation in the near-tip region of UPVC, and components of COD, which is perpendicular to the crack surface, should be the predominant controlling parameter of crack propagation.